Investigating the correlation between the five major personality traits and a student’s online habits - Siti Maisarah Zurkarnain; Abdulsahib, Aws A. (Penerbit Universiti Kebangsaan Malaysia, 2023)
The increasingly widespread use of e-learning and the internet, in general, has reached the point where it should become a cause of concern towards a student’s online habits. By having bad habits online, students could risk the occurrence of data lost or a data breach occurring. Hence, this study was done in order to further investigate this potential factor. The objective of this study is to be able to identify which personality traits could potentially cause an effect on a student’s online habits and what must be done in order to improve said student’s online habits. This study has deployed surveys within a primary and secondary education grade within Al-Noor International School. These surveys serve as a measuring tool to evaluate a student’s personality traits and online habits. The results of this survey are then used to observe the relationship between the two variables and draw a conclusion on the investigation. This study is done in hopes to bring more attention towards the personality traits of students and how moderation can be done to further help protect the students as well as the educational institutions as a whole in order to preserve such data.